Cyclic Behavior of Bolted Extended End-Plate Moment Connections with Different Sizes of End Plate and Bolt Stiffened by a Rib Plate - Abbas Haghollahi; Reza Jannesar (Salehan Institute of Higher Education, 2018)
This paper presents a numerical study on the behavior of prequalified Bolted Extended End Plate (BEEP) moment connections when are affected by cyclic loading. Specimens were six four-bolt extended end-plate connections consist of H-shaped columns and I-shaped beams with different geometry as well as different end-plate size and bolt diameter; three of them were stiffened by a triangular rib plate welded to the top and bottom of the beam flanges, and others remained unstiffened. They were modeled in ABAQUS software and their cyclic behavior was evaluated using finite element analysis. Responses of specimens were examined by presenting their equivalent plastic strain, stress distribution, and moment-rotation hysteretic curves. Results revealed that with the increase of beam height and inertia moment in equal story drift rotations, the reduction of connection strength occurred earlier due to the occurrence of local buckling in the beam web and flange after subjecting to cyclic loading. By comparing moment-rotation hysteretic responses of specimens, it was found out that in unstiffened BEEP connections with thinner end-plate, the use of single vertical rib stiffener can slightly improve their cyclic behavior, but in connections with thicker end plate, it showed no considerable effect. It was concluded that the BEEP connections whose dimensions are not based on the tenth code of the Iranian national building regulations, cannot satisfy the criteria of AISC seismic provisions for both special and intermediate steel moment frames, although they experienced no local beam web and flange buckling.